Pemanfaatan Sampah Plastik Kemasan dan Perca Untuk Kreatifitas Ekonomis Kelompok PKK - Emi Roslinda; Tri Widiastuti; Diana Citra; Duma Elsya; Indahyana (Universitas Lancang Kuning, 2022)
Almost all human and household activities produce waste. The largest source of waste comes from household activities, so waste is an environmental problem that needs attention from all stakeholders. The government has issued various regulations to manage waste by applying the 3R (reduce, reuse, and recycle) concept, especially inorganic waste. Based on these problems, a solution is needed to help waste processing at the household level by empowering PKK mothers through increasing knowledge of the use and processing of inorganic waste in the form of plastic and patchwork. Activities are carried out in the form of socialization and demonstration, mentoring, and evaluation. Evaluation is done by distributing questionnaires at the beginning and end of the activity. The general results show an increase in knowledge of the use and processing of plastic and patchwork waste.